RELEVANSI KESEJAHTERAAN EKONOMI KELUARGA DENGAN PENINGKATAN PERCERAIAN DI KABUPATEN BONE - Marzuki, Sitti Nikmah (Pasca Sarjana STAIN Watampone, 2016)
The problem then arises is the welfare of the family, if husbend can not perform its responsibility to make a living